Special issue of the 2nd International Conference on Computational Mathematics and Engineering Sciences (CMES2017) - Bulut, Hasan C; Gurefe, Yusuf B; Akturk, Tolga (My University, 2017)
In this study, a new approach that assumes u f u ? ? ?cos? ?? and u f u ? ? ?sinh ? ?? is applied to construct the traveling wave solutions of the (N + 1)-dimensional double sine-Gordon and (N + 1)-dimensional double sinh-coshGordon equations. Some new elliptic integral function solutions are respectively obtained by this method, and then these solutions are converted into the Jacobi elliptic function solutions. According these results, one can easily see that this method is very effective mathematical tool for the (N+1)-dimensional nonlinear physical problems.
Keywords: Fizik; Uygulamalı; Matematik